Criminal Responsibility for Perpetrators of Pornography Crimes - Berly Usmany; Hadibah Zachra Wadjo; Elias Zadrach Leasa (LUTUR Law Journal, 2025)
This article analyzes the process of determining a suspect through a preliminary examination process against a perpetrator of a crime based on applicable legal regulations. Determination of a suspect as referred to, is carried out through a case title mechanism. The purpose of this writing is to examine and analyze the criminal responsibility of the perpetrators in the pornographic videos that are distributed and to analyze and analyze the judge's considerations in imposing criminal sanctions on the perpetrators of the pornographic videos that are distributed. The research method used in analyzing and discussing this research is a type of normative legal research that uses secondary legal materials as initial data to then be continued with primary legal materials or field data and tertiary legal materials that support and provide an understanding of primary legal materials and secondary legal materials over other legal materials. The legal materials that are prioritized come from literature studies, relying on scientific books such as criminal law literature, scientific magazines, and documents, then using three research approaches consisting of the Legislation approach, conceptual approach, and case approach. The results of the study show that a person being named a suspect must go through an examination process and must have at least 2 (two) sufficient pieces of evidence to prove that a crime has indeed occurred and the person suspected of committing the crime has been supported by 2 (two) pieces of evidence that can justify the occurrence of a crime and Legal Efforts against the determination of a suspect without an examination process, namely through Pretrial Legal Efforts and Civil Legal Efforts.